2014 World Congress on Computing and Communication Technologies 2014
DOI: 10.1109/wccct.2014.89
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Feature Extraction from Cervical Cytology Images by Gaussian Mixture Model

Abstract: In this paper, methods for automated extraction of multiple features of cytoplasm and nuclei from cervical cytology images are described. Edges of the image are enhanced by Edge Sharpening filter. Then Gaussian mixture model using Expectation Maximization and K-means clustering is used to segment the image into its components as background, nucleus and cytoplasm. Features have been identified for both multiple and single cervical cytology cells. For multiple cell images, nucleus to cytoplasm ratio is calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…Many authors have proposed solutions to this problem of detecting cervical cells, using synthetic databases or working with databases that do not represent the reality of conventional Pap smear images, in which there are many cells, often overlapping, in a single image [16][17][18][19][20][21][22][23][24]. Therefore, the investigation of methodologies capable of being applied in the real context of cervical cancer screening is still a great challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have proposed solutions to this problem of detecting cervical cells, using synthetic databases or working with databases that do not represent the reality of conventional Pap smear images, in which there are many cells, often overlapping, in a single image [16][17][18][19][20][21][22][23][24]. Therefore, the investigation of methodologies capable of being applied in the real context of cervical cancer screening is still a great challenge.…”
Section: Introductionmentioning
confidence: 99%
“…They used 20 morphologic features and found that the combinations of algorithms Bagging + MultilayerPerceptron and AdaBoostM1 + LMT were the best scenarios analyzed by them. [20] presented a method to extract nuclei and cytoplasm features of Pap smear images. Attributes such as center, perimeter, area, and average intensity were considered.…”
Section: Introductionmentioning
confidence: 99%
“…So for a detection system of cervical cell images, representations of cells seek to capture the differences between normal and abnormal classes. Several studies have investigated methods for feature representation [16][17][18][19], and previous methods perform well in different aims of the cervical cell analysis. In particular, textural features were ever used to extract nuclei characteristics [19].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated methods for feature representation [16][17][18][19], and previous methods perform well in different aims of the cervical cell analysis. In particular, textural features were ever used to extract nuclei characteristics [19]. The chromatin texture of the nucleus exhibits the essential pre-cancerous changes and can be applied to detect abnormal cells too.…”
Section: Introductionmentioning
confidence: 99%
“…Örnek olarak, hücre çekirdeklerinin bölütlenmesi için alçak geçirgen gürültü giderici filtrenin ardından iteratif eşikleme [5], yıldız şekil öncülleri temelinde yönlü türevler yardımıyla görüntü işleme tabanlı yaklaşımla bölütlenmesi [6], çok-adımlı aşama seviye kümesi yöntemi yaklaşımları kullanılmıştır [7]. Hücre çekirdeği ve sitoplazmasının bölütlenmesi için piksel yoğunluklarına bağlı Gauss karışım modeli çoklu özellik çıkarım yöntemleri kullanılarak uygulanmıştır [8]. Ayrıca, hücre çekirdeği ile sitoplazmasını birbirinden ayırmak için gradyan vektör alanı (GVF) yılan yöntemi [9], hücre kümesi ile görüntü arka planını birbirinden ayırmak için minimum hata eşiklemesi [10] ve şekil-bilimsel geriçatım ve kümeleme yöntemlerinden yararlanılmıştır [11].…”
Section: Introductionunclassified